CARACTERIZACIÓN ANÁTOMO-HISTOPATOLÓGICA DE ENTEROPATÍAS CAUSANTES DE MORTALIDAD EN CRÍAS DE ALPACA - Palacios E., César (2005)
A total of 48 intestinal samples of new born alpacas which died due to diarrhea processes were evaiuated. Samples collected during the dry season (June-August, 2002) were from animals belonging to the Experimental Research Statiori of IVITA, La Raya, Cnsco, and &ose collected during the pamtntion scason (Febmary, 2003) were from a fanners community inNuiioa, Puno. Topographic intestinal samples were tjken, fixed in 15% fomalinen solution and stained with H-E. Thiriy seven cases were compatible with bacteria1 omcesses. where 30 of k m were due to enterotoxemia and the other 7 were processes complicated with colibacilosis. Only two of these cases wereassociated with Cqptosporidirim sp. Four cases were related with Eimeria macusaniensis and enterotoxemia and ?cases wirh E. maarsanensis and E. prrnoensis. OnIy 4 cases were observed in association witb E. larnae. This is the first report of intracellular forms of E. ivitaensis in Lieherkhün glands of yeyuno and iieum, and extracellular foms of E. macusaniensis in smal intcstine, ceca1 and ascendent colon.